The interplay of food-related lifestyle and eating behavior in Italian women - Hamam, Manal; D’Amico, Mario; Spina, Daniela; La Via, Giovanni; Di Vita, Giuseppe (Frontiers in Nutrition, 2024)
Introduction Women play a crucial role in food shopping and preparation, and their food choices have significant implications for their health and that of their families. This study aims to provide a perspective on women’s eating lifestyle, which has undergone significant changes. Methods A factor analysis was conducted to assess the degree of involvement in food choices and the types of food items consumed among a sample of 399 Italian women. Results Through cluster analysis, four segments were identified: hedonic food consumers, sustainable- and balanced-diet consumers, food experimenters, and no food fondness consumers. The results reveal a correlation between the degree of food involvement and the type of food consumed. Discussion Furthermore, the food lifestyle of the sample is partially dependent on age. Individuals aged 25–28 years show more hedonic food consumption behavior, while the older age group (44–64 years) falls into the sustainable and balanced diet consumer cluster (the largest cluster) and the cluster of those who do not express definable food choices (no food fondness).